2015
DOI: 10.4103/2152-7806.159382
|View full text |Cite
|
Sign up to set email alerts
|

Selective dorsal rhizotomy for spastic diplegia secondary to stroke in an adult patient

Abstract: Background:Selective dorsal rhizotomy (SDR) is often recommended for children with spastic paraparesis and cerebral palsy. SDR reduces spasticity in the lower extremities for these children with spastic paraplegia. However, SDR is infrequently recommended for adults with spasticity. Spastic diplegia in adult patients can be due to stroke, brain or spinal cord injury from trauma, infection, toxic-metabolic disorders, and other causes. Although rarely considered, SDR is an option for adult patients with spastic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…No change in tone post-SDR was reported in 24.6% (n = 35). Six of 12 publications documented changes in spasticity using the modified Ashworth score (MAS) [8][9][10][11][12][13]. Analysis of adult patients in these publications showed that SDR led to marked reduction in the spasticity of the hip flexors, hip adductors, hamstrings, quadriceps, and gastrocnemius/soleus muscles (Table 3).…”
Section: Efficacy Of Sdr On Managing Spasticity/tonementioning
confidence: 99%
See 1 more Smart Citation
“…No change in tone post-SDR was reported in 24.6% (n = 35). Six of 12 publications documented changes in spasticity using the modified Ashworth score (MAS) [8][9][10][11][12][13]. Analysis of adult patients in these publications showed that SDR led to marked reduction in the spasticity of the hip flexors, hip adductors, hamstrings, quadriceps, and gastrocnemius/soleus muscles (Table 3).…”
Section: Efficacy Of Sdr On Managing Spasticity/tonementioning
confidence: 99%
“…The pain profile before and after SDR was recorded in 7 publications (n = 86) [9,10,[12][13][14][15][16]. After SDR, lower limb muscle and joint pain was completely eliminated in 4.7% (n = 4).…”
Section: Pain and Sensory Deficitmentioning
confidence: 99%
“…Eppinger et al [51] describe a patient who suffered from hypertension and a hemorrhagic stroke at the age of 46 who underwent SDR (L1-S1). The surgery was performed after two failed intrathecal baclofen pump placements due to repeated infections.…”
Section: Secondary Lower Extremity Spasticitymentioning
confidence: 99%
“…The study by Chan et al mentioned a participant with hereditary spastic paraparesis (HSP), in addition to 20 individuals with CP. 7 Although CP diagnosis was one of the inclusion criteria of this review, SDR can also be indicated for patients with spasticity resulting from other diagnoses such as multiple sclerosis, Leigh syndrome, 25 stroke, 26 spinal cord injury 24 , and transverse myelitis. 27 …”
Section: Data Synthesismentioning
confidence: 99%